Thermal injury after “huffing” compressed air duster: a case report - Jared Katz; Alyrene Dorey (Toxicology Communications, 2024)
Recreational abuse of compressed air duster has been associated with cardiac toxicity, central nervous system depression, local tissue damage, seizures, and death. We describe a 30-year-old man who reported huffing four bottles of canned air duster to “get high.” In addition to blistering on his dominant hand, he developed pain and swelling of the lips and tongue, followed by difficulty speaking and swallowing. He underwent endotracheal intubation for anticipated airway failure and was treated for an allergic reaction. Fiberoptic bronchoscopy and computed tomography scan of the neck demonstrated unaffected posterior oropharynx and airways. He was extubated on hospital day 2 and subsequently made a full recovery. Patients with oropharyngeal and dermal injury after abuse of compressed air duster are likely suffering a thermally-mediated injury. Outcomes are generally good with minimal intervention. Routine treatment for an allergic reaction is unnecessary.